On the properties of hot forged Ti-6Al-4V alloy aimed for surgical implants - Mihailović, Marija; Patarić, Aleksandra (Metallurgical and Materials Engineering, 2019)
The investigation here is aimed to examine the structural and mechanical changes that might have occurred during the hot forging process, a process to obtain a surgical hip implant, and the subsequent heat treatment. Microstructural characterization, morphological and semi-quantitative chemical analyses have been accomplished using an optical and scanning electron microscope. Chemical analyses of all surfaces obtained by the dotted method in all analyzed samples have shown the approximate equal content of aluminum, titanium, vanadium, iron, and silicon. Tensile testing and measurements were following obtained microstructure, showing the uniformity of microstructure and properties along the forging part, as well as over its cross section. All tests proved that hot forging could be a suitable procedure for surgical implants processing.